The remains of a prehistoric dugout from Skorbičy (Družba) Village in the Buh River region - Asheichyk, Vitali U.; Beliavets, Vadzim G. (Journal of the Belarusian State University. History, 2020)
The article discusses the remains of a prehistoric dugout discovered at the edge of a sand quarry near Skorbičy (Družba) Village, Brest District, Belarus in 2013. It was impossible to extract and conserve the boat due to heavy decomposition of wood, but its shape and design features were documented during the archaeological excavations. The boat measured 3.75 × 0.65 m was made from hollowed pine trunk. There were bulkheads near the boat’s bow and stern, and there was a low rib along the bottom on the inside. The bottom and boards were most likely tarred on the outside. There were some dozens of fieldstones inside the boat, on its bow and stern. Some of them were burnt. Five small potsherds of the Iron Age were found in the eastern part of the dugout. Three radiocarbon datings were obtained for the samples of wood from the dugout. Two datings are almost identical and date the boat back from 480 to 210 cal BC. The third one is discordant and has calibrated range from 200 BC to 80 AD. Considering the archaeological context and the results of previous investigations of the archaeological sites in Skorbičy, the earlier dating could be assumed. The dugout is most probably connected with the population of the Pomeranian culture.
Keywords: dugout canoe; Early Iron Age; Pomeranian culture; Belarus